Deaf person's perception of care in health services (Research, Society and Development, 2022)
Objective: To investigate the perception of deaf people about the care offered when they seek health services. Method: Exploratory and descriptive research, with a qualitative approach, based on Bardin's Content Analysis method, using the data saturation method. Results: Eight deaf people participated in the research. The lack of communication is the biggest complaint among users. The deaf person is not given the opportunity to express their opinions and doubts regarding the health problem, and this role is always delegated to another person, and when this person is not present, care is compromised. Final considerations: Barriers to access imply important losses and indicate the professionals' lack of preparation in the work process. Therefore, adjustments regarding the way of assisting deaf clients need to be rethought, in order to guarantee them safe and qualified assistance.